The cytotoxic effect and glucose uptake modulation of Baeckea frutescens on breast cancer cells - Shahruzaman, S. H.; Mustafa, Mohd Firdaus; Ramli, Salfarina; Maniam, Sandra (BMC, 2019)
Background: Baeckea frutescens (B. frutescens) of the family Myrtaceae is a plant that has been used in traditionalmedicine. It is known to have antibacterial, antipyretic and cytoprotective properties. The objective of this study isto explore the mechanism of B. frutescens leaves extracts in eliminating breast cancer cells. Method: B. frutescens leaves extracts were prepared using Soxhlet apparatus with solvents of different polarity. The selective cytotoxicity of these extracts at various concentrations (20 to 160 μg/ml) were tested using cell viability assay after 24, 48 and 72 h of treatment. The IC50 value in human breast cancer (MCF-7 and MDA-MB-231) and mammary breast (MCF10A) cell lines were determined. Apoptotic study using AO/PI double staining was performed using fluorescent microscope. The glucose uptake was measured using 2-NBDG, a fluorescent glucose analogue. The phytochemical screening was performed for alkaloids, flavonoids, tannins, triterpenoids, and phenols. Results: B. frutescens leaves extracts showed IC50 value ranging from 10 -127μg/ml in MCF-7 cells after 72 h of treatment. Hexane extract had the lowest IC50 value (10μg/ml), indicating its potent selective cytotoxic activity. Morphology of MCF-7 cells after treatment with B. frutescens extracts exhibited evidence of apoptosis that included membrane blebbing and chromatin condensation. In the glucose uptake assay, B. frutescens extracts suppressed glucose uptake in cancer cells as early as 24 h upon treatment. The inhibition was significantly lower compared to the positive control WZB117 at their respective IC50 value after 72 h incubation. It was also shown that the glucose inhibition is selective towards cancer cells compared to normal cells. The phytochemical analysis of the extract using hexane as the solvent in particular gave similar quantities of tannin, triterpenoids, flavonoid and phenols. Presumably, these metabolites have a synergistic effect in the in vitro testing, producing the potent IC50 value and subsequently cell death. Conclusion: This study reports the potent selective cytotoxic effect of B. frutescens leaves hexane extract against MCF-7 cancer cells. B. frutescens extracts selectively suppressed cancer cells glucose uptake and subsequently induced cancer cell death. These findings suggest a new role of B. frutescens in cancer cell metabolism